Clinical Implementation of Second-generation Minimally Invasive Image-guided Cochlear Implantation Surgery. Issue 5 (June 2021) - Labadie, Robert F.; Riojas, Katherine; Von Wahlde, Kathleen; Mitchell, Jason; Bruns, Trevor; Webster, Robert; Dawant, Benoit; Fitzpatrick, J. Michael; Noble, Jack
Abstract : Objective: Minimally invasive, image-guided cochlear implantation (CI) surgery consists of drilling a precise tunnel from the surface of the mastoid cortex through the facial recess to target the scala tympani. In the first set of clinical trials of this technique, heat-induced facial nerve paresis (House-Brackmann II/VI) occurred on a patient on the last day of the initial trial which was scheduled to be halted secondary to a change in the regulatory requirements dictated by the 2012 the Food and Drug Administration Safety and Innovation Act requiring Investigational Device Exemption approval for previously exempted customized medical device testing. To address this adverse event, extensive changes were made to the drilling protocol; additionally, a custom insertion tool was developed. To address the Food and Drug Administration Safety and Innovation Act, an Investigational Device Exemption was submitted and, subsequently approved. Herein is described our first clinical implementation of the modified technique. Patient: Seventy-year-old with profound, postlingual sensorineural hearing loss who had previously undergone right CI via traditional approach in 2015. Intervention: Minimally invasive image-guided left CI. Main Outcome Measure: Time of intervention, final location of CI electrode array within cochlea. Results: Surgery took 155 minutes of which the largest components (in descending order) were soft tissue work, closure, and drilling. Full scala tympani insertion with angular insertion depth of 557 degrees of the electrode array was achieved. There were no complications, and the patient had an uneventful recovery and activation. Conclusions: Minimally invasive, image-guided CI surgery is achievable and reduces the mastoid depression associated with traditional CI surgery. ClinicalTrials.gov information: Study NCT03101917, Microtable Microstereotactic Frame and Drill Press and Associated Method for Cochlear Implantation Level of Evidence: Case Report. Abstract : Supplemental Digital Content is available in the text